An investigation on the seismicity and seismic gaps in the Indo-Myanmar border region - Kalita, S; Barman, NC (Journal of Nepal Geological Society, 2008)
The Indo-Myanmar border region is a complex geotectonic setting due to the interaction between the active north-south convergence along the Himalayas and the eastwest convergence and folding within the Indo-Burman ranges with very high seismicity. It belongs to the north-south trading Indo-Myanmar Orogenic Belt. The elongated region within 20°-28°N latitudes and 93°-98°E longitudes shows that the region is seismically active and maximum number of earthquakes falls on and around the Eastern Boundary Thrust (EBT) that is parallel to Indo-Burma plate boundary and Shan Boundary Fault (SHF) towards the southern portion of the belt. On the other hand, less number of earthquakes fall in and around schuppen belt towards northwest of the study region. The epicentral map of the region shows an elongated narrow zone of concentration of epicenters with significant variation of seismic activity in its different sections, which might be due to the local differential geology (rock properties) along the arc and differences in the generation of stress in different section of the arc. On the basis of this variation pattern of epicentral density, the belt can be divided into three tectonic blocks - Block-I (20°–22.5°N), Block-II (22.5°– 25°N) and Block-III (25°–28°N). The concentration of earthquakes is found more in the central portion of the elongated belt, which may indicate accelerated convergence process. Moreover, the geographical and the depth distributions of earthquakes clearly reflect the tectonic behaviour of the region. Epicentral plots of the earthquakes (Me”5 mb) in the latitude-time (year) domain for the period 1964-2005 show some elliptical gaps of different sizes at different locations and time span. However, no definite pattern can be visualized and therefore, it is very difficult to explain the occurrences and the seismic potential of these gaps. As per present situation the gap region is prominent around latitude 22°N in which there is a possibility of occurrence of a major earthquake in near future. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.14